Cost-effectiveness analysis of trastuzumab deruxtecan versus trastuzumab emtansine for HER2-positive breast cancer - Yang, Jiangping; Han, Jiaqi; Zhang, Yalan; Muhetaer, Muhelisa; Chen, Nianyong; Yan, Xi (Frontiers in Pharmacology, 2022)
Background: The DESTINY-Breast03 clinical trial demonstrated that trastuzumab deruxtecan (T-DXd) outperformed trastuzumab emtansine (T-DM1) in progression-free survival (PFS) in patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (mBC). Considering the excessive cost of antibody-drug conjugates, the clinical value of T-DXd must be assessed by both its efficacy and cost. We compared the cost-effectiveness of T-DXd and T-DM1 for patients with HER2-positive mBC pretreated with anti-HER2 antibodies and a taxane from the perspectives of the United States (US) and China. Methods: A comprehensive Markov model based on the DESTINY-Breast03 phase III randomized clinical trial was used to compared the cost and effectiveness of T-DXd and T-DM1 for HER2-positive mBC. Data on direct medical cost and utilities were collected from published literatures. The recorded data included the costs, quality-adjusted life-year (QALY), incremental cost-effectiveness ratio (ICER) and incremental net health benefit (INHB). Sensitivity analysis was conducted to measure the potential uncertainty due to parameter variability. Additional subgroup cost-effectiveness analysis was performed. Results: Treatment of HER2-positive mBC with T-DXd gained 0.73 QALYs compared with T-DM1 strategy. The incremental cost was 59,942 in the US, with an ICER of 82,112/QALY and an INHB of 0.33 QALYs, respectively. In China, the incremental cost of T-DXd versus T-DM1 was 222,680, with an ICER of 305,041/QALY and a negative INHB of -5.18 QALYs. At willingness-to-pay (WTP) threshold of 150,000/QALY in the US and 37,653/QALY in China, the probability of T-DXd as the dominant option was 77.5% and 0.1%, respectively. The unit price of T-DXd greatly influenced the results according to one-way sensitivity analysis. To meet the 50% or 90% chance of being cost-effective, the estimated cost of T-DXd would need to be less than 17.24/mg and 12.06/mg in China, respectively. Conclusion: T-DXd is more cost-effective than T-DM1 for patients with HER2-positive mBC in the US, but not in China at current drug prices.